$1 (BTwas the night b$1 (Bfore Christmas :s an African-American version - Rosales, Melodye; Moore, Clement Clarke, 1779-1863. (New York : Scholastic, 1996)
Presents a turn-of-the-century black family$1 (Bs encounter with St. Nick as he delivers his presents before flying off into the night.s
"Based on the original poem, A visit from St. Nicholas, by Clement C. Moore."
Keywords: African American families -- Juvenile poetry; Santa Claus -- Juvenile poetry; Christmas -- Juvenile poetry; Children$1 (Bs poetry, American.s; African Americans -- Poetry; Santa Claus -- Poetry; Christmas -- Poetry; American poetry; Narrative poetry